A szovjet–kelet-európai viszony átalakulása a korai Hruscsov korszakban - Békés, Csaba; Kalmár, Melinda (Acta Scientiarum Socialium, 2016)
The transformation of the Soviet-East-European relationship in the early Khrushchev era. This article first revisits the relations between Moscow and its East Central European allies in the period following Stalin’s death. The authors argue that after 1953 the multilateralization of this relationship gave rise to the gradual emancipation of these countries vis-a-is the West, the Third Word states and the Soviet Union itself. In the second part of the article the authors analyze the importance of the first Soviet Bloc summit meeting following the Hungarian Revolution in 1956 which took place in Budapest in early January, 1957. The authors argue that the meeting represents the genesis of the Brezhnev doctrine as the participants jointly decided, for the first time in the history of the Eastern Bloc, on two fundamental issues concerning Hungarian internal political developments: they rejected the plan to introduce a pseudo multiparty system and decided on launching a court procedure against the Imre Nagy group, eventually resulting in the execution of the former prime minister and his associates.